2014
DOI: 10.12968/jowc.2014.23.11.532
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a thin absorbent skin adhesive dressing for wound management

Abstract: The dressing was well-received by both clinicians and patients in all fifteen cases. The thin absorbent skin adhesive dressing was found to be a promising new technology that could offer significant advantages to improve the quality, cost, and convenience of wound care. Further work is underway to validate these findings in larger and more homogeneous patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…It was found that after drying, both parameters (thickness and weight of the BC obtained from various cultivation conditions) were comparable, although the difference was statistically significant. The abovementioned property of RMF-modified cellulose may find particular application in the design of absorbent dressings used for the treatment of highly exudating chronic wounds (Alvarez, Phillips, Menzoian, Patel, & Andriessen, 2012;Stephen-Haynes, Callaghan, Wibaux, Johnson, & Carty, 2014). The moisture is essential to normal wound healing process, however, excessive amount of exudate can be detrimental and is considered as wounding agent itself by some authors (Trengrove, Bielefeldt-Ohmann, & Stacey, 2008;Adderley, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that after drying, both parameters (thickness and weight of the BC obtained from various cultivation conditions) were comparable, although the difference was statistically significant. The abovementioned property of RMF-modified cellulose may find particular application in the design of absorbent dressings used for the treatment of highly exudating chronic wounds (Alvarez, Phillips, Menzoian, Patel, & Andriessen, 2012;Stephen-Haynes, Callaghan, Wibaux, Johnson, & Carty, 2014). The moisture is essential to normal wound healing process, however, excessive amount of exudate can be detrimental and is considered as wounding agent itself by some authors (Trengrove, Bielefeldt-Ohmann, & Stacey, 2008;Adderley, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, our novel BC biomaterials released the absorbed water slowly, thanks to preserved micro-porous structure. These properties make the developed BC materials very promising for applications as wound dressings not only for highly-exuding, but also dry wounds (85,86). Moisture is an essential factor of wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, our novel BC biomaterials released the absorbed water slowly, thanks to preserved nano-porous structure. These properties make the developed BC materials very promising for applications as wound dressings not only for highly-exuding, but also dry wounds [95,96]. Moisture is an essential factor of wound healing process.…”
Section: Discussionmentioning
confidence: 99%